Intergenerational mobility in Latin America: The multiple facets of social status and the role of mothers - Matías Ciaschi; Mariana Marchionni; Guido Neidhöfer (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2023)
In this paper we assess intergenerational mobility in terms of education and income rank in five Latin American countries-Brazil, Chile, Ecuador, Mexico, and Panama-by accounting for the education and occupation of both parents. Based on the method proposed by Lubotsky and Wittenberg (2006), we find that intergenerational persistence estimates increase by 26% to 50%when besides of the education of parents we consider also their occupation. The increase is partic-ularly strong when education is more evenly distributed in the parents' generation. Furthermore, we evaluate the changing importance of each single proxy for parental background to explain inter-generational mobility patterns in each country and over time, and find that the relative importance of the characteristics of mothers have been increasing over the last decades, in line with rising women's average years of education and labor market participation. Interesting heterogeneities across countries and cohorts are observed.
Keywords: D63; J62; O15; 330; Intergenerational Mobility; Education; Occupation; Mothers; Latin America